(3bUI Jeje Hf MHjH GdOGQjs - (3eLghds ((3eMeO GdegOhjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfbGFd gPg GdMcGjI GdYLjHI Efg deG cGf aj CjGe NdGaI YeQ Hf GdNWGH QVj Gddg Yfg LGFJ GeQCI CfUGQjI JTch dg CeQ HYdgGs
(3BNQgG (B:s
(3ef CQGO Cf jUGaM hjfXQ Edi Cdg GdLfI adjUGag hdjfXQ Edi Jeje Hf MHjH GdOGQjs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJGQjNs